The Role of Fluorine-18-Fluorodeoxyglucose Positron Emission Tomography in Aggressive Histological Subtypes of Thyroid Cancer: An Overview - Giorgio Treglia; Salvatore Annunziata; Barbara Muoio; Massimo Salvatori; Luca Ceriani; Luca Giovanella (International Journal of Endocrinology)
Aggressive histological subtypes of thyroid cancer are rare and have a poor prognosis. The most important aggressive subtypes of thyroid cancer are Hürthle cell carcinoma (HCTC) and anaplastic and poorly differentiated carcinoma (ATC and PDTC). The American Thyroid Association recently published guidelines for the management of patients with ATC, but no specific guidelines have been done about HCTC. We performed an overview of the literature about the role of Fluorine-18-Fluorodeoxyglucose positron emission tomography or positron emission tomography/computed tomography (FDG-PET or PET/CT) in aggressive histological subtypes of thyroid cancer. Only few original studies about the role of FDG-PET or PET/CT in HCTC, PDTC, and ATC have been published in the literature. FDG-PET or PET/CT seems to be useful in staging or followup of invasive and metastatic HCTC. FDG-PET or PET/CT should be used in patients with ATC in initial staging and in the followup after surgery to evaluate metastatic disease. Some authors suggest the use of FDG-PET/CT in staging of PDTC, but more studies are needed to define the diagnostic use of FDG-PET/CT in this setting. Limited experience suggests the usefulness of FDG-PET or PET/CT in patients with more aggressive histological subtypes of DTC. However, DTC presenting as radioiodine refractory and FDG-PET positive should be considered aggressive tumours with poor prognosis.